2017
DOI: 10.1515/fsmu-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

An overview of adaptative responses to drought stress in Eucalyptus spp.

Abstract: Eucalyptus is a plant frequently present and cultivated in arid regions because of its high adaptation to drought. Furthermore, it is known by its numerous species which represents a great opportunity to choose several tolerant species with variable uses. Therefore, the choice of species, hybrids or genotypes resistant to aridity becomes a necessity before any plantation in regions and countries characterized by semi-arid, arid and Saharan climates. Our review shows an important effect of drought on anatomical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 51 publications
0
28
0
1
Order By: Relevance
“…At the region of provenance level, the trees from the Eyre Peninsula exhibited lower growth in height and diameter, were slenderer, and had harder wood, while trees from Kangaroo Island exhibited less slender phenotypes and better growth (in height and diameter), and the wood of their trunks had greater pilodyn penetration. Several studies have shown that the relationship between height, diameter, and wood density in Eucalyptus is associated with variations in drought tolerance [ 25 , 26 , 34 , 35 ]. According to several studies, the diameter of xylem vessels and the growth rate in trees are positively correlated [ 30 , 31 , 32 ], implying that taller trees tend to have a lower wood density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the region of provenance level, the trees from the Eyre Peninsula exhibited lower growth in height and diameter, were slenderer, and had harder wood, while trees from Kangaroo Island exhibited less slender phenotypes and better growth (in height and diameter), and the wood of their trunks had greater pilodyn penetration. Several studies have shown that the relationship between height, diameter, and wood density in Eucalyptus is associated with variations in drought tolerance [ 25 , 26 , 34 , 35 ]. According to several studies, the diameter of xylem vessels and the growth rate in trees are positively correlated [ 30 , 31 , 32 ], implying that taller trees tend to have a lower wood density.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, as water availability decreases, trees become shorter and have higher-density wood [ 26 , 33 ]. Several studies have shown that the relationship between tree height (HT) and wood density is associated with the variation in drought tolerance [ 25 , 26 , 34 , 35 ]. In this context, the trade-off between growth and wood properties may be regulated by pleiotropic genes that control the mechanisms of adaptation to drought in woody species [ 26 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Climate data show that such events have increased globally in the last few decades and models predict further increases in drought frequency and severity into the future (Intergovernmental Panel on Climate Change, 2014). As long-lived sessile organisms, many forest tree species are likely to have developed a range of adaptations to aid survival and recovery following drought (Hamanishi & Campbell, 2011;Saadaoui, Yahia, Dhahri, Jamaa, & Khouja, 2017). Common garden experiments have shown that significant genetic-based variation in such traits may exist within forest tree species, with provenance-level variation in drought susceptibility, or associated functional traits (Dutkowski & Potts, 2012;McLean et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus species are generally characterized by a great ability of water absorption, as well as a great resistance to the dry conditions. This quality is manifested in morphological and physiological parameters, including root development and changes in osmotic potential, stomatal conductance, gas exchange, transpiration rates and photosynthesis (Saadaoui et al, 2017). The use of Eucalyptus for reforestation under reduced water conditions, essentially with climate change impacts, would pose problems related mainly to its water consumption, biodiversity reduction and environment degradation (Zhang, 2012).…”
Section: Effect Of Salt Stress and Osmotic Potential On Germination Omentioning
confidence: 99%